Réponses

2014-03-22T11:03:13+01:00
2x+3 = 5  ou x-3 = 5
2x= 5-3            x= 5-(-3)
 2x=2              x= 8
  x=2/2
   x=1

 donc S = { 1 ;8 }
  • Utilisateur Brainly
2014-03-22T12:00:02+01:00
Résolution:
En quelle classe es-tu ?
Si tu es au moins en première:

(2x+3) (x-3) = 5 
(2x+3) (x-3) -5 = 0 ⇒ On regroupe tout dans le même membre (côté)
2x² -6x +3x -9 -5 = 0
2x² -3x -14 = 0

Δ= (-3)² -4* 2*(-14)
Δ= 9 + 112
Δ= 121
Δ > 0 Donc il y a deux solutions
√Δ = 11

x₁ = (3 -11)/ 4 = -7/4

x₂ = (3+11) / 4 = 14/4 = 7/2

Donc S= ( -7/4 ; 7/2)